Phase-channel dynamics reveal the role of impurities and screening in a quasi-one-dimensional charge-density wave system - M. D. Thomson (Nature Portfolio, 2017)
Abstract Charge density waves (CDWs), i.e. the periodic spatial modulation of coupled electronic and lattice density, are ubiquitous in low-dimensional conductors and have taken on renewed relevance due their role in state-of-the-art materials, e.g. high-T c superconductors, topological insulators and low-dimensional carbon. As CDWs are described by a complex order parameter to represent both the amplitude and phase, they are formally analogous to BCS superconductors and spin-waves, providing a prototype of collective phenomena for the further development of field theories and ab-initio calculations of complex solids. The low-energy excitations are mixed electron-phonon quanta which ideally separate into an amplitude and phase channel, and provide a sensitive probe of the ground state and non-equilibrium dynamics, including ultrafast photoinduced phase transitions. While recent studies of the amplitude modes have brought substantial progress aided by a phenomenological Ginzburg-Landau framework, we focus here on the phase modes using ultrafast terahertz spectroscopy. Experiments on K0.3MoO3 provide a more complete picture, and reveal a high sensitivity to interactions with impurities and screening effects from photogenerated carriers, both of which can be accounted for by generalizations of the model. Moreover, our considerations emphasize the need to revisit the treatment of inherent electronic damping in quantum-mechanical CDW theories.